THE BENEFITS OF STRATEGIC HOMOGENEITY AND STRATEGIC HETEROGENEITY: THEORETICAL AND EMPIRICAL EVIDENCE RESOLVING PAST DIFFERENCES - Dooley, Robert S.; Fowler, Dorn M.; Miller, Alex (Strategic Management Journal, 1996)
Past research on the relationship between strategic variety and industry profitability has argued for either high homogeneity or high heterogeneity. In this paper, we review the literature on strategic variety and use it to develop hypotheses suggesting that the relationship between strategic variety and average industry profits is curvilinear. Based on our analysis of 61 industries, we find empirical support for our hypotheses, suggesting that very high levels of heterogeneity or homogeneity are more likely associated with industry profitability, while the industries in our sample displaying moderate levels of strategic variety are most likely to suffer from widespread financial losses.